Pengaruh Penerapan Sistem IPAL terhadap Kulitas Air Buangan Rumah Pemotongan Hewan - Naura Nisrine Hidayatullah; Tuhu Agung Rachmanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT X is a company engaged in animal slaughtering and produces liquid waste in the process of its activities. Located in Banyuwangi Regency, East Java Province, this study aims to determine the effect of the implementation of the Wastewater Treatment Plant (WWTP) system on the quality of PT X's wastewater. The effect of implementing the WWTP system can be measured through baseline data collection, evaluation of WWTP effectiveness, observation of WWTP operation and maintenance, and recommendations in accordance with the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 68 of 2016 concerning Domestic Wastewater Quality Standards. Pollutant parameters in wastewater include BOD, COD, TSS, and O&G (Oil & Grease) that exceed the quality standards. After the implementation of the WWTP system, the effluent results showed a decrease and no longer exceeded the quality standards, proving that the implemented WWTP system has a positive effect on the quality of the PT X abattoir discharge water.